Semantik eine Einführung - Löbner, Sebastian 1949- (De Gruyter, 2015)
The book offers an up-to-date introduction to the essential phenomena, issues, and theoretical approaches of linguistic semantics. It covers the key aspects of word and sentence semantics. In his step-by-step development of the theme, the author puts great stock in the consistency, coherence, and understandability of the scientific approach. The new edition has been extensively revised, expanded, and updated
Keywords: Sprache, Linguistik; Linguistics and Semiotics -- Levels of Linguistic Analysis -- Semantics; Linguistics and Semiotics -- Theoretical Frameworks and Disciplines -- Linguistics, other; Semantik; Lehrbuch